Estimating hospital inpatient cost-savings with sucroferric oxyhydroxide in patients on chronic hemodialysis in five European countries: a cost analysis. (1st January 2021) - Herrero, Jose Antonio; Salomone, Mario; Ramirez de Arellano, Antonio; Schaufler, Thilo; Walpen, Sebastian
Abstract: Aims: Hyperphosphatemia is common among patients with advanced chronic kidney disease (CKD) undergoing dialysis. The iron-based phosphate binder (PB), sucroferric oxyhydroxide (SO), has a low daily pill burden and is indicated for the control of serum phosphorus in these patients. In a retrospective database study, hemodialysis patients switched to long-term SO therapy had fewer hospitalizations compared with patients switched to other PB therapies. This economic analysis aimed to quantify potential cost-savings of reduced hospitalizations associated with SO for healthcare systems in five European countries. Materials and methods: All-cause hospital admissions incidence data were sourced from a real-world retrospective database study comparing adult, in-center hemodialysis patients maintained on 2 years of SO therapy (mSO) versus patients who discontinued SO (dSO) within 90 days of their first prescription and switched to other PBs. A literature search was conducted to determine the cost per hospital admission for dialysis patients in the healthcare setting of each European country. A cost-model combined the incidence rate of all-cause hospital admissions and the cost per admission to estimate the country-specific inpatient costs for the mSO and dSO groups. Results: Annual inpatient cost-savings per patient in the mSO group versus the dSO group were €1, 201, €2, 097, €2, 059, €1, 512, and €3, 068 in France, Germany, Italy, Spain, and the UK, respectively. When annual PB drug costs per patient were considered, the net annual economic cost-savings per patient were €327, €1, 585, €1, 022, €1, 100, and €2, 204, respectively. Limitations: Hospital admissions data used in the analysis were observational in nature and derived from a US hemodialysis patient population; the effect of SO therapy on hospitalization rates for US and European hemodialysis patients may differ. The analysis did not consider indirect healthcare costs associated with hospitalizations. Conclusion: SO therapy may offer substantial inpatient cost-savings by reducing all-cause hospital admissions attributable to uncontrolled hyperphosphatemia.